TINJAUAN YURIDIS TERHADAP PENANGGUHAN PENAHANAN DENGAN JAMINAN (STUDY DI POLRESTA BARELANG) - Supianto Supianto (Faculty of Law - Tarumanagara University, 2020)
The type of research in this thesis is empirical juridical research is the way or procedure used to solve the problem of research by researching secondary data first to then examine the primary data in the field. This research is a type of empirical legal research that is research in the form of empirical studies to find theories about the process of happening and about the process of working the law within the community. The result of this research is that the legal effect on the guarantor of suspension of detention if the suspect flees the guarantor must pay the amount determined by the competent authority and the consideration of the investigator in granting suspension of detention all depending on the background of the guarantor and the commission of the crime committed by the suspect and terms specified.